The mixed-complementary approach to specifying agricultural supply in computable general equilibrium models - Lofgren, Hans; Robinson, Sherman (International Food Policy Research Institute, 1997)
In Computable General Equilibrium (CGE) models, it is typically assumed that agricultural resources are smoothly substitutable in neoclassical functions, with flexible prices generating market equilibrium in a setting with full resource employment. Such a specification is often inadequate, especially for analyses of agricultural supply issues. With more disaggregation, the use of smooth, twice-differentiable, production or cost functions to specify agricultural technology is increasingly unrealistic. The purpose of this paper is to show how CGE models formulated as mixed-complementarity (MC) problems can incorporate more realistic, specifications of agricultural supply, drawing on the extensive literature on mathematical programming models applied to agriculture. We extend a stylized standard neoclassical CGE model to a CGE-MC model that includes Leontief (activity-analysis) technology, endogenous determination of the market regime for agricultural factors (unemployment or full employment), and inequality constraints on agricultural factor use. In an analysis of reduced agricultural water supplies in Egypt, we show how such a model can generate realistic results concerning water use and productivity that cannot be captured in a standard CGE model. The main conclusion is that, in analyses focused on agricultural supply issues, CGE-MC models that selectively incorporate features from the mathematical-programming literature offer a powerful alternative to standard models.